ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI SHU KOPERASI WERDDHI DANA JAGADHITA DI KELURAHAN BANYUNING KECAMATAN BULELENG KABUPATEN BULELENG - I GUSTI AYU LIA YASMITA; NI MADE TAMAN AYUK (GANEC SWARA, 2024)
This study aims to determine the effect of capital, number of members, and total credit on the Net Remaining Results of Operations (SHU). The object of research is the Werddhi Dana Jagadhita Cooperative in Banyuning Village, Buleleng District, Buleleng Regency. The data source in this study is secondary data over the last three years, from 2021-2023, which was taken directly from the research location at the Werddhi Dana Jagadhita Cooperative in Buleleng Regency. The research method is quantitative using Multiple Linear Regression Analysis. The results of partial hypothesis testing (t-test) show that there is a positive and significant influence between capital, number of members, and amount of credit on SHU at the Werddhi Dana Jagadhita Cooperative in Banyuning Village, Buleleng District, Buleleng Regency. The F-test results show that collectively the variables of capital, number of members, and amount of credit have a significant effect on SHU at the Werddhi Dana Jagadhita Cooperative in Banyuning Village, Buleleng District, Buleleng Regency.